Breast cancer screening knowledge among Hungarian women: a cross-sectional study - Diána Reményi Kissné; Noémi Gede; Zsolt Szakács; István Kiss (BMC, 2021)
Abstract Background Breast cancer (BC) is the leading malignant tumor among women worldwide. Although attending regular BC screening effectively reduces cancer-related mortality, surveys testify that screening knowledge is critically low among women. We aimed to conduct a comparative cross-sectional survey to assess BC and BC screening-related knowledge in Hungary. Methods Women between 25 and 65 years of age without a previous history of malignant tumors were included with non-probability sampling in 2017. Respondents were recruited either from primary care (laywomen) or from the waiting rooms of mammography (screening attendees). A self-completion questionnaire was constructed with questions about BC (risk factors, signs and symptoms, curability, and mortality), BC screening (mammography and breast self-examination), and BC-related information sources to assess knowledge among laywomen and screening attendees. In addition to descriptive statistics, odds ratios with 95% confidence intervals were calculated in univariate analysis and logistic regression was used in multivariate analysis. Results Altogether, 480 women completed the questionnaire, of which 429 (227 laywomen and 202 screening attendees) were eligible for inclusion. Laywomen and screening attendees knew the recommended age at first mammography in 35.2% and 86.6%, the recommended frequency of screening in 33.9% and 12.9%, the recommended age at first breast-self examination in 38.8% and 51.2%, had sufficient knowledge of the risk factors of BC in 7.0% and 5.9%, and that of signs and symptoms of BC in 16.7% and 28.9%, respectively. A higher proportion of screening attendees correctly identified the recommended age of first BC screening correctly than that of laywomen (86.6% vs. 35.2%; p < 0.001). The most popular information sources were television among laywomen and general practitioners or specialists among screening attendees. In multivariate analysis, older age, higher education, and place of residency were significant predictors of the right answers. Conclusions Although knowledge was insufficient in almost all fields of the questionnaire, the most prominent gap was observed concerning risk factors and signs and symptoms of BC both in laywomen and, unexpectedly, screening attendees. Most laywomen were lacking knowledge of screening protocol. These results urge breast health and BC knowledge interventions in Hungary.